Images beyond History. Jean Baudrillard’s Apocaliptic Pharmacology - Cardone, Luca; Mollisi, Matteo Angelo (Mechane, 2022)
The aim of our article is to highlight the key contribution of one of the fundamental categories of Jean Baudrillard’s thought, namely that of “hyperreality”, to the reflection on the post-historical character of the contemporary Western form of life. By highlighting the “pharmacological” feature of the historical dialectic defined by this concept, we will find its most significant divergence from the better-known pharmacology of Jacques Derrida and Bernard Stiegler in the fact that a common appeal to the Heideggerian motif of the “Zusammengehörigkeit”, redefined as a structural co-implication of empowerment and weakening of faculties and characters of experience as technically mediated, is used by Baudrillard to describe not so much the constitutive externalisation of the mnestic faculties, and thus the tendency towards oblivion that derives from it, but rather the structural eclipse of the real in the empowerment already always offered by its simulacrum. This is the theoretical core that allows Baudrillard’s theses on the progressive expulsion of the negative from the virtual image, eminent condition of the onset of that “excess of positivity” that would characterise our post-historical stage, to add an extremely original chapter to a whole constellation of reflections on the mediation of contemporary devices that can be dated back at least to Benjamin, as well as to give a problematic apocalyptic twist to the pharmacological approach and its consequent “immunitarian” reading of actuality.